Genetic progress estimates obtained by tis EPAMIG paddy rice improvement program in the eighties - Soares, Antônio Alves; Ramalho, Magno Antônio Patto; de Sousa, Augusto ferreria (Pesquisa Agropecuaria Brasileira, 1994)
This study was performed aiming to estimate genetic progress accomplished by the paddy rice improvement program in Minas Gerais State, in the eighties. Data (average grain yield) were obtained from cultivars and pure lines from advanced comparative trials at EPAMIG from 1979/80 to 1988/89. Total genetic gain was 742,1 kg/ha, which gives an average annual gain of 1,6%. Some alternatives to improve the Minas Gerais program are suggested.